Regra-matriz de incidência tributária como inference ticket - Cabral, Pedro Henrique de Araújo (2014)
It is research function of linguistic Tax Incidence Rule-Matrix (general and abstract rule) through the dialectical confrontation of concepts brought by the theory of Paulo de Barros Carvalho with notions and tools of theoretical decent post by Marcelo Lima War, which concern notion of norms as Inferential Frame. Usually identifies general and abstract norm as a kind of prescription, linguistic arrangement expressive of a command. However, the contributions of studies in philosophy of language and philosophy of mind, allow to reassess the status of the legal norm in relation to its linguistic function, through the handling of instruments rarely used in traditional juridical doctrine. Thus, with this new theoretical tool, is undertaken to demonstrate that the function of such a rule-Matrix, far from expressing a prescription, in fact, meets the relevant and intriguing role Inference Ticket in the context of the legal justification of the behavior of users the tax law.